Proceedings of the 2nd International Conference on Electronic Engineering and Renewable Energy Systems ICEERE 2020, 13-15 April 2020, Saidia, Morocco - Hajji, Bekkay; Mellit, Adel.; Marco Tina, Giuseppe; Rabhi, Abdelhamid; Launay, Jerome; Naimi, Salah Eddine; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book includes papers presented at the Second International Conference on Electronic Engineering and Renewable Energy (ICEERE 2020), which focus on the application of artificial intelligence techniques, emerging technology and the Internet of things in electrical and renewable energy systems, including hybrid systems, micro-grids, networking, smart health applications, smart grid, mechatronics and electric vehicles. It particularly focuses on new renewable energy technologies for agricultural and rural areas to promote the development of the Euro-Mediterranean region. Given its scope, the book is of interest to graduate students, researchers and practicing engineers working in the fields of electronic engineering and renewable energy. .
PART I: Communication, Networks and Information technology -- PART II: Materials and Devices Applications -- PART III: Electronics, Circuits and Systems -- PART IV : Robotics, Mechatronics, Control and Instrumentation -- PART V: Electric Vehicle -- PART VI : Power Electronics, Systems and Applications -- PART VII: Control Systems -- PART VIII : Renewable Energy.
Keywords: Renewable energy resources; Electrical engineering; Electronics; Microelectronics; Control engineering; Robotics; Mechatronics; Artificial intelligence; Signal processing; Image processing; Speech processing systems; Renewable and Green Energy; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation; Control, Robotics, Mechatronics; Artificial Intelligence; Signal, Image and Speech Processing